Evolusi Gerakan Sosial Keagamaan: Studi Kepustakaan Tentang Kontribusi Walubi dalam Pembangunan Masyarakat Inklusif - Alda Malik Fadillah; Anya Dwi Aprillia; Putri Zahra; Mh Farhan; Fika Fahriza; Indra harahap (STID Raudlatul Iman Sumenep, 2026)
This article examines the transformation of the Indonesian Buddhist Community Representative (Walubi) from a representative-bureaucratic entity into a socio-religious driving actor through the praxis of Engaged Buddhism. Utilizing a Systematic Literature Review (SLR) method that adapts the PRISMA protocol, this research synthesizes academic literature published from 2005 to 2026 to dissect Walubi's social maneuvers in the public sphere. The results indicate that Walubi's contribution to building an inclusive society in Indonesia manifests in three movement typologies: (1) cross-boundary health philanthropy that effectively deconstructs stereotypes of minority exclusivity; (2) disaster emergency response mobilization utilizing the liminality phase to weave communal solidarity; and (3) nonviolent structural diplomacy within the Religious Harmony Forum (FKUB). Sociologically, these maneuvers successfully mitigate primordial prejudice through intense cultural interactions. However, this study also finds that inclusion built upon philanthropic schemes leaves an asymmetrical class power relation, risking becoming a